Maturity evaluation of orthodontically important anatomic structures with computed tomography - Ok, Gokcen; YILMAZ, BERZA; YILMAZ, BERZA; AKSOY, DİRENÇ ÖZLEM; AKSOY, DİRENÇ ÖZLEM; Kucukkeles, Nazan (My University, 2021)
Background/objectives: The success of the orthopaedic treatment is closely related to the patient-s skeletal maturation. This study aimed to evaluate the midpalatal suture (MPS), the zygomaticomaxillary suture (ZMS) maturation, and the closure degree of the spheno-occipital synchondrosis (SOS) in patients of different age groups. The presence of a correlation between these parameters and the palatal dimensions was also verified.